Об одной шекспировской цитате в «Поэме без героя» [A Shakespeare Quote in “Poem without a Hero”] - Salman, Marina (Slavica Revalensia, 2014)
The purpose of this article is to explain Anna Akhmatova’s decision to rewrite the following stanza from “Poema bez geroia” (1940—1962): Ne otbit’sia ot rukhliadi pestroi, Eto staryi chudit Kaliostro Za moiu k nemu neliubov’. I mel’kaiut letuchie myshi, I begut gorbuny po krysheI tsyganochka lizhet krov’. The final version of the stanza — Ne otbit’sia ot rukhliadi pestroi. Eto staryi chudit Kaliostro — Sam iziashneishii satana, Kto nad mertvym so mnoi ne plachet, Kto ne znaet, chto sovest’ znachit I zachem sushchestvuet ona. — alludes to Shakespeare’s Sonnet 151. The penultimate line of the final version of the stanza (“Kto ne znaet, chto sovest’ znachit…”) paraphrases the opening line of the sonnet (“Love is too young to know what conscience is…”); the sonnet’s keywords — “love,” “conscience,” “young,” “guilty of my faults” — correspond to the central themes of Poem without a Hero.